Long-term maintenance treatment of psoriasis: the role of calcipotriol/betamethasone dipropionate aerosol foam in clinical practice - Gabriella Fabbrocini; Clara De Simone; Paolo Dapavo; Perigiorgio Malagoli; Alessandro Martella; Piergiacomo Calzavara-Pinton (Journal of Dermatological Treatment)
Most patients with psoriasis present with localized mild-to-moderate disease. In this case, the application of topical treatments in the first-line setting is recommended in most cases.Among different topical options, the fixed-dose combination of betamethasone dipropionate (BD) and vitamin D analogue (Cal) aerosol foam (Enstilar®, Leo Pharma) is approved as first-line topical therapy for the treatment of psoriasis in USA and the EU, due to its high efficacy and its favorable administration scheme.The PSO-LONG was the first trial to report on the long-term efficacy and safety of the Cal/DB foam treatment for the proactive management of psoriasis and now, the indications of Cal/BD foam included its use in the psoriasis maintenance treatment. However, the precise role of this treatment and the potential therapeutic schemes in the long-term management of psoriasis need further clarification.This Position Paper, authored by a group of Italian Expert Dermatologists, critically discusses the long-term management of psoriasis with Cal/BD foam in clinical practice. In particular, the biological rationale in the proactive treatment with Cal/BD foam and current evidence regarding this therapeutic approach are presented, along with its application also in patients with moderate-to-severe disease, difficult-to-treat lesions, or within combination regimens. In addition, strategies to improve adherence to long-term treatment of psoriasis are discussed,